Advances in the development of biodegradable coronary stents: A translational perspective. (December 2022) - Zong, Jiabin; He, Quanwei; Liu, Yuxiao; Qiu, Min; Wu, Jiehong; Hu, Bo
Abstract: Implantation of cardiovascular stents is an important therapeutic method to treat coronary artery diseases. Bare-metal and drug-eluting stents show promising clinical outcomes, however, their permanent presence may create complications. In recent years, numerous preclinical and clinical trials have evaluated the properties of bioresorbable stents, including polymer and magnesium-based stents. Three-dimensional (3D) printed-shape-memory polymeric materials enable the self-deployment of stents and provide a novel approach for individualized treatment. Novel bioresorbable metallic stents such as iron- and zinc-based stents have also been investigated and refined. However, the development of novel bioresorbable stents accompanied by clinical translation remains time-consuming and challenging. This review comprehensively summarizes the development of bioresorbable stents based on their preclinical/clinical trials and highlights translational research as well as novel technologies for stents (e.g., bioresorbable electronic stents integrated with biosensors). These findings are expected to inspire the design of novel stents and optimization approaches to improve the efficacy of treatments for cardiovascular diseases. Graphical abstract: Image 1 Highlights: Bioresorbable stents can overcome the limitations of non-degradable stents. 3D printing of shape-memory polymeric stents can lead to better clinical outcomes. Advances in Mg-, Fe- and Zn-based stents from a translational perspective. Electronic stents integrated with biosensors can covey stent status in real time. Development in the assessment of stent performance in vivo.